Stock Market Price and Its Determinants: A Case Study of Nigerian Banks - John, Onyedikachi O. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
Financial firms in a country make a substantial fraction of its equity market. The present study is aimed at examining the factors that influence stock prices with reference to Nigerian banks. Twelve commercial banks in Nigeria are considered for this study for 2012 and 2013. Using linear regression model and partial correlation, the results indicate that for both years considered, net asset value per share and price-book value ratio are strongly correlated with stock market price, and are having significant influence on the stock price. However, dividend per share and price-earnings ratio are significant in 2013, but insignificant in 2012.